2017
DOI: 10.1021/acs.analchem.7b01452
|View full text |Cite
|
Sign up to set email alerts
|

Nondestructive Redox Quantification Reveals Glassmaking of Rare French Gothic Stained Glasses

Abstract: The sophisticated colors of medieval glasses arise from their transition metal (TM) impurities and capture information about ancient glassmaking techniques. Beyond the glass chemical composition, the TM redox is also a key factor in the glass color, but its quantification without any sampling is a challenge. We report a combination of nondestructive and noninvasive quantitative analyses of the chemical composition by particle-induced X-ray emission–particle-induced γ-ray emission mappings and of the color and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 56 publications
1
26
0
Order By: Relevance
“…This shows that the relative quantities of Cu and Fe in the glass recipe were a critical parameter to control the final glass color from blue‐green (D2) to green (F3). Previous results on a complex medieval glass have also suggested that color control was achieved by a precise control of the added oxide quantities . The few published chemical compositions for ancient green glasses have shown that, whatever the composition type (soda, lime, potash etc), while the Fe 2 O 3 content is in the range of 0.4‐0.8 wt%, the CuO content is often larger than 2 wt%, which is much larger than the concentration used in this study.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…This shows that the relative quantities of Cu and Fe in the glass recipe were a critical parameter to control the final glass color from blue‐green (D2) to green (F3). Previous results on a complex medieval glass have also suggested that color control was achieved by a precise control of the added oxide quantities . The few published chemical compositions for ancient green glasses have shown that, whatever the composition type (soda, lime, potash etc), while the Fe 2 O 3 content is in the range of 0.4‐0.8 wt%, the CuO content is often larger than 2 wt%, which is much larger than the concentration used in this study.…”
Section: Discussionmentioning
confidence: 59%
“…This redox equilibrium is at the origin of the “glassmaker soap” process, which consists in the addition of manganese to glass colored by iron impurities. Iron in glass is partly present as divalent cations resulting in a greenish color . Addition of manganese results in the oxidation of iron into trivalent poorly coloring iron ions and thus removes the greenish hue of the glass.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the interpretation of the glass hue by the naked eye is subjective, so that colour description of ancient glass is highly operator dependent (Johnston-Feller 2001). In such context, it should be stressed that determination of the oxidation state of transition metal ions in ancient glass, to determine causes of colour, is a long standing question and previous studies on this topic were carried out mainly by means of X-ray absorption spectroscopy and/or other techniques, such as optical absorption spectroscopy and electron paramagnetic resonance, and were focused on a large variety of ancient glasses not only dated to Roman times but also to the Middle Ages (e.g., (Azzoni et al 2005;Quartieri et al 2005;Bingham and Jackson 2008;Meulebroeck et al 2010;Gliozzo et al 2010;De Ferri et al 2011;Arletti et al 2013;Ceglia et al 2014Ceglia et al , 2016Möncke et al 2014;Zoleo et al 2015;Hunault et al 2016Hunault et al , 2017Capobianco et al 2019). It should also be highlighted that, with optical and X-ray spectroscopies, the determination of the redox ratio of iron is easier than for other metals such as manganese (Bamford 1977;Bidegaray et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Among the IBA methods, RBS (Rutherford Backscattering Spectroscopy) is frequently used for precise and acc , while Nuclear Reaction Analysis (NRA) and/or Particle Induced Gamma Ray Emission (PIGE) can be used to quantify concentrations of light elements, such as D, Be, C, O, Mg, and Na. Simultaneously, Particle Induced X sed to quantify Na and heavier elements [21][22][23][24][25] . Microprobe IBA methods have also been used in the past for .…”
Section: Methodsmentioning
confidence: 99%